2017
DOI: 10.1038/srep40736
|View full text |Cite
|
Sign up to set email alerts
|

Correlated electronic decay in expanding clusters triggered by intense XUV pulses from a Free-Electron-Laser

Abstract: Irradiation of nanoscale clusters and large molecules with intense laser pulses transforms them into highly-excited non- equilibrium states. The dynamics of intense laser-cluster interaction is encoded in electron kinetic energy spectra, which contain signatures of direct photoelectron emission as well as emission of thermalized nanoplasma electrons. In this work we report on a so far not observed spectrally narrow bound state signature in the electron kinetic energy spectra from mixed Xe core - Ar shell clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…The X-ray pulse arrival time for the same electron bunch is locked to the respective THz pulse down to a few femtoseconds due to natural synchronization (Frü hling et al, 2009;Tavella et al, 2011;Oelze et al, 2017).…”
Section: Characterization Of Thz Doubler Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray pulse arrival time for the same electron bunch is locked to the respective THz pulse down to a few femtoseconds due to natural synchronization (Frü hling et al, 2009;Tavella et al, 2011;Oelze et al, 2017).…”
Section: Characterization Of Thz Doubler Radiationmentioning
confidence: 99%
“…The X-ray free-electron laser FLASH1 at DESY in Hamburg, Germany, has a worldwide unique feature -a THz undulator behind the main X-ray undulator section, that allows users to perform pump-probe experiments with ultrashort highintensity THz and soft X-ray pulses (Gensch et al, 2008;Frü hling et al, 2009;Tavella et al, 2011;Stojanovic & Drescher, 2013;Oelze et al, 2017). The wavelength range can be tuned from 1 to 300 mm (1 to 300 THz), depending on the electron beam energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b). Generally, the electron emission can be attributed to correlated electronic decay processes, where one electron relaxes from an excited to the ground state and transfers the excess energy to a second electron that leaves the cluster [31,32]. Since in the discussed processes an inner-valence vacancy is filled, they can more specifically be described as Auger decay [37], which, to our knowledge, has not been previously observed following ionization of clusters by intense NIR pulses.…”
mentioning
confidence: 99%
“…Previous studies have shown that only those nonradiative decay processes, which occur at least a few picoseconds after the laser pulse has ended, can be identified in electron kinetic energy spectra [17,18,31,32]. At earlier times, the cluster potential strongly influences the kinetic energies of emitted electrons.…”
mentioning
confidence: 99%